Effects of oxidized and reduced forms of methylthioninium in two transgenic mouse tauopathy models. Issue 4 (June 2015) - Melis, Valeria; Magbagbeolu, Mandy; Rickard, Janet E.; Horsley, David; Davidson, Kathleen; Harrington, Kathleen A.; Goatman, Keith; Goatman, Elizabeth A.; Deiana, Serena; Close, Steve P.; Zabke, Claudia; Stamer, Karsten; et al.
Abstract : Given the repeated failure of amyloid-based approaches in Alzheimer's disease, there is increasing interest in tau-based therapeutics. Although methylthioninium (MT) treatment was found to be beneficial in tau transgenic models, the brain concentrations required to inhibit tau aggregation in vivo are unknown. The comparative efficacy of methylthioninium chloride (MTC) and leucomethylthioninium salts (LMTX; 5–75 mg/kg; oral administration for 3–8 weeks) was assessed in two novel transgenic tau mouse lines. Behavioural (spatial water maze, RotaRod motor performance) and histopathological (tau load per brain region) proxies were applied. Both MTC and LMTX dose-dependently rescued the learning impairment and restored behavioural flexibility in a spatial problem-solving water maze task in Line 1 (minimum effective dose: 35 mg MT/kg for MTC, 9 mg MT/kg for LMTX) and corrected motor learning in Line 66 (effective doses: 4 mg MT/kg). Simultaneously, both drugs reduced the number of tau-reactive neurons, particularly in the hippocampus and entorhinal cortex in Line 1 and in a more widespread manner in Line 66. MT levels in the brain followed a sigmoidal concentration–response relationship over a 10-fold range (0.13–1.38 μmol/l). These data establish that diaminophenothiazine compounds, like MT, can reverse both spatial and motor learning deficits and reduce the underlying tau pathology, and therefore offer the potential for treatment of tauopathies.